Abnormal lens morphogenesis and ectopic lens formation in the absence of beta-catenin function - Kreslova, Jana; Machon, Ondrej; Ruzickova, Jana; Lachova, Jitka; Wawrousek, Eric F; Kemler, Rolf; Krauss, Stefan; Piatigorsky, Joram; Kozmik, Zbynek (Genesis (New York, N.Y., 2007)
beta-Catenin plays a key role in cadherin-mediated cell adhesion as well as in canonical Wnt signaling. To study the role of beta-catenin during eye development, we used conditional Cre/loxP system in mouse to inactivate beta-catenin in developing lens and retina. Inactivation of beta-catenin does not suppress lens fate, but instead results in abnormal morphogenesis of the lens. Using BAT-gal reporter mice, we show that beta-catenin-mediated Wnt signaling is notably absent from lens and neuroretina throughout eye development. The observed defect is therefore likely due to the cytoskeletal role of beta-catenin, and is accompanied by impaired epithelial cell adhesion. In contrast, inactivation of beta-catenin in the nasal ectoderm, an area with active Wnt signaling, results in formation of crystallin-positive ectopic lentoid bodies. These data suggest that, outside of the normal lens, beta-catenin functions as a coactivator of canonical Wnt signaling to suppress lens fate.
Keywords: signální transdukce; nemoci nosu; Cell Adhesion; myši transgenní; choristom; Choristoma; Signal Transduction; Mice; oční čočka; Morphogenesis; beta Catenin; zvířata; Eye; Lens, Crystalline; Nose Diseases; myši; morfogeneze; buněčná adheze; oči; Wnt Proteins; beta-katenin; Mice, Transgenic; proteiny Wnt; Animals